2023
DOI: 10.1158/1055-9965.epi-22-0793
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Stage at Diagnosis and Survival among Women ≥65 Years in California

Abstract: Background: Through adequate screening and follow-up, cervical cancer can be prevented or detected at early-stage (stage I), which is related to excellent survival. Current guidelines recommend discontinuing screening for women ≥65 years with history of normal Pap and/or HPV tests, potentially leaving this age group vulnerable. This study examined late-stage disease in a population-based cohort. Methods: Using California Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…A study by Cooley et al. 15 delves into the prevalence of late‐stage cervical cancer in women aged 65 and older, a demographic often overlooked in screening guidelines. Analyzing data from the California Cancer Registry spanning 2009 to 2018, it reveals that a substantial proportion of older women present with late‐stage disease compared to younger counterparts, leading to lower survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Cooley et al. 15 delves into the prevalence of late‐stage cervical cancer in women aged 65 and older, a demographic often overlooked in screening guidelines. Analyzing data from the California Cancer Registry spanning 2009 to 2018, it reveals that a substantial proportion of older women present with late‐stage disease compared to younger counterparts, leading to lower survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Uninsured and publicly insured patients have a higher relative risk of late stage cervical cancer diagnosis than privately insured patients 12 . Disparities in age exist, as 20% are diagnosed at older than 65 years with worse survival outcomes 13 . Data are limited on whether these cases are due to new HPV infections, inadequate screening history, or lack of appropriate follow-up and whether current guidelines to stop screening after age 65 years need adjustment 14 …”
Section: Cervical Cancermentioning
confidence: 99%
“…Socioeconomic inequities, as measured by variables such as median family income and poverty level, are thought to be a mediator of these findings 4 . Other studies have shown that disparities in screening and insurance status are associated with diagnoses of advanced‐stage cervical cancer among Hispanic/Latinx populations 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…4 Other studies have shown that disparities in screening and insurance status are associated with diagnoses of advanced-stage cervical cancer among Hispanic/Latinx populations. 6,7 The U.S. Hispanic/Latinx population is the fastest-growing ethnic minority group and, by 2050, is expected to exceed a population of 102 million people from over a dozen countries of origin. 8 Health data for Hispanic/Latinx populations are typically presented in aggregate, which masks the population's significant heterogeneity.…”
Section: Introductionmentioning
confidence: 99%